Answer with explanation:
Using Sine Rule for Congruence of Triangles
[tex]\Rightarrow\frac{a}{\ SinA}=\frac{b}{\ Sin B}=\frac{c}{\ Sin C}\\\\\Rightarrow\frac{15}{\ Sin29^{\circ}}=\frac{20}{\ Sin B}\\\\\Rightarrow\frac{15}{0.49}=\frac{20}{\ Sin B}\\\\\Rightarrow \ SinB=\frac{20 \times 0.49}{15}\\\\\Rightarrow \ SinB=\frac{9.8}{15}\\\\\Rightarrow \ SinB=0.65\\\\B=41^{\circ}[/tex]
Using Angle Sum Property of Triangle
⇒∠A+∠B+∠C=180°
⇒29°+41°+∠C=180°
⇒∠C=180°-70°
⇒∠C=110°
→Again Using Sine Rule
[tex]\Rightarrow \frac{b}{\ Sin B}=\frac{c}{\ Sin C}\\\\\Rightarrow \frac{20}{\ Sin 41^{\circ}}=\frac{c}{\ Sin 110^{\circ}}\\\\\Rightarrow \frac{20}{0.65}=\frac{c}{0.94}\\\\\Rightarrow \frac{20 \times 0.94}{0.65}=c\\\\\Rightarrow c=\frac{18.8}{0.65}\\\\\Rightarrow c=28.92[/tex]
Length of third Side =28.92 unit
So,Perimeter of Triangle
=Sum of sides of triangle
=a +b +c
=15 + 20 +28.92
= 63.92 unit
Answer:
b on edge
Step-by-step explanation:
Find the discriminant of 5x^2+3x-5=0 for x
For this case we have that by definition, a quadratic equation is of the form:
[tex]ax ^ 2 + bx + c = 0[/tex]
Its roots are given by:
[tex]x = \frac {-b \pm \sqrt {b ^ 2-4 (a) (c)}} {2a}[/tex]
By definition, the discriminant is given by:
[tex]D = b ^ 2-4 (a) (c)[/tex]
According to the given equation we have to:
[tex]a = 5\\b = 3\\c = -5[/tex]
Substituting:
[tex]D = 3 ^ 2-4 (5) (- 5)\\D = 9 + 100\\D = 109[/tex]
Answer:
The discriminant is 109
AD diameter of Circle P, if m 1 = 40 then m AB = 20, 40, 80 PLEASE HELP
Answer:
40 it is a trick question
Step-by-step explanation:
Answer:
The correct option is: 40
Step-by-step explanation:
Measure of an arc is actually the measure of the central angle corresponding with that same arc.
Here, the corresponding central angle for arc [tex]\widehat{AB}[/tex] is [tex]\angle1[/tex].
Given that, [tex]m\angle 1= 40[/tex]°
So.....
[tex]m\widehat{AB}=m\angle 1\\ \\ m\widehat{AB}=40\°[/tex]
What is the value of x?
a)20
b)35
c)60
d)70
Answer:
x is equal to 20, or the answer A
Step-by-step explanation:
They are opposite angles so they are equal to each other. When you set up the equation (x+40)=3x, you get the answer to be 20. hope this helped!
For this case we have to define by opposite angles the vertex that:
[tex]x + 40 = 3x[/tex]
Subtracting 3x on both sides of the equation:
[tex]x-3x + 40 = 0\\-2x + 40 = 0[/tex]
Subtracting 40 from both sides of the equation:
[tex]-2x = -40[/tex]
Dividing between -2 on both sides of the equation:
[tex]x = \frac {-40} {- 2}\\x = 20[/tex]
So, we have that [tex]x = 20[/tex]
ANswer:
[tex]x = 20[/tex]
What’s the answer please help
Answer:
[tex]\boxed{\text{A. }\math{\left \{ x \, | \, x \in \mathbb{R}, x < -2 \right \}}}}[/tex]
Step-by-step explanation:
The open circle means that the point is not included in the solution set, and the arrow pointing left means that all numbers less than -2 are members.
In set-builder notation, each term has a special meaning. The braces enclose the members of the set.
Here's how you translate the notation,
[tex]\begin{array}{rcl}\\\left \{ & = & \text{The set of}\\x & = & \text{all x values}\\| & = &\text{such that}\\x & = & x\\\in & = &\text{is a member of}\\\mathbb{R}, & = &\text{all real numbers, and}\\x < -2 & = & \text{x is less than -2}\\\end{array}\\\text{The answer is }\boxed{\textbf{A. }\mathbf{\left \{ x \, | \, x \in \mathbb{R}, x < -2 \right \} }}}[/tex]
helpppp
Which statement is true about the effects of the transformations on the graph of function f to obtain the graph of function g.
g(x) = f(x - 3) + 4
A.. The graph of function fis shifted left 3 units and down 4 units.
B. The graph of function is shifted right 3 units and down 4 units.
C. The graph of function is shifted left 3 units and up 4 units.
D. The graph of function fis shifted right 3 units and up 4 units.
The statement which is rue about the effects of the transformations on the graph of function f to obtain the graph of function g is D. The graph of function f(x) is shifted right 3 units and up 4 units.
What is Geometric Transformation?Transformation of geometrical figures or points is the manipulation of a given figure to some other way.
Different types of transformations are Rotation, Reflection, Glide reflection, Translation and Dilation.
Given is a function f(x) and the transformed function g(x) = f(x - 3) + 4.
After translation, the original figure is shifted from a place to another place without affecting it's size.
Here the transformation is both horizontal and vertical translation.
f(x) is first changed to f(x - 3).
When f(x) is changed to f(x - d), the function is shifted right d units.
So here the function is shifted right to 3 units.
Similarly when f(x) changed to f((x) + d, then the function is shifted up d units.
So the function is also shifted up 4 units.
Hence the transformation is the graph is shifted right to 3 units and up 4 units.
Learn more about Transformations here :
https://brainly.com/question/23760922
#SPJ7
I'm just done with math... as long as you explain it I'll mark your brainiest.
Answer:
The correct answer is the third option
Step-by-step explanation:
Have different slope but have the same y-intercept, so they have no solution.
y = 1/2x - 3
To graph this, the slope 1/2 which means go up once and to the right twice and b = -3, which means the y-intercept.
second equation:
y = -1/2x -3
To graph this, the slope -1/2 which means go down once and to the right twice and b = -3, which means the y-intercept.
Please mark as brainliest
What is the solution to the equation fraction 4 over 5 n minus fraction 1 over 5 equals fraction 2 over 5 n?
1 )n = −2
2) n = 4
3 )n = fraction 1 over 2
4) n = fraction 2 over 3
Answer:
value of n = 2
Step-by-step explanation:
[tex]\frac{4}{5n}-\frac{1}{5}=\frac{2}{5n}[/tex]
We need to solve the above equation.
Find Least Common multiplier from 5n, 5 = 5n
Multiply both sides of the equation by 5n
[tex]\frac{4}{5n}*5n-\frac{1}{5}*5n=\frac{2}{5n}*5n\\Solving:\\4 -n = 2\\[/tex]
Now finding the value of n.
Adding -4 on both sides
[tex]4 -n-4 = 2-4\\-n= -2[/tex]
Multiplying both sides by -1
n = 2
The value of n is 2.
We can verify by putting value of n in the given question.
[tex]\frac{4}{5n}-\frac{1}{5}=\frac{2}{5n}\\n=2\\\frac{4}{5*2}-\frac{1}{5}=\frac{2}{5*2}\\\frac{4}{10}-\frac{1}{5}=\frac{2}{10}\\\frac{2}{5}-\frac{1}{5}=\frac{1}{5}\\\frac{2-1}{5}=\frac{1}{5}\\\frac{1}{5}=\frac{1}{5}[/tex]
So, value of n = 2
Answer:
It's C : n=1/2
Have a great day :)
What is the answer to this question
Answer:
The 4 pack is the better deal.
Step-by-step explanation:
You need to divide the amount of cost by the number of rolls per pack to get a per roll price.
4 pack = $2.04
$2.04/4 rolls = cost $.51/roll
for the 9 pack $4.68.
$4.68/4 rolls = $.52/1 roll
The better deal is the 4 pack because $.51 is less than $.52 per roll for the 9 pack.
If F(x) = 2x-5 and G(x) = x2 + 1, what is G(F(x))?
The equation for [tex]\( G(F(x)) = 4x^2 - 20x + 26 \)[/tex].
To find [tex]\( G(F(x)) \)[/tex], we first need to substitute the expression for [tex]\( F(x) \)[/tex] into the function [tex]\( G(x) \)[/tex].
Given:
[tex]\[ F(x) = 2x - 5 \]\[ G(x) = x^2 + 1 \][/tex]
Replace x in [tex]\( G(x) \)[/tex] with [tex]\( F(x) \):[/tex]
[tex]\[ G(F(x)) = (2x - 5)^2 + 1 \][/tex]
Now, expand [tex]\( (2x - 5)^2 \)[/tex] using the binomial theorem:
[tex]\[ (2x - 5)^2 = (2x - 5)(2x - 5) \]\[ = 4x^2 - 10x - 10x + 25 \]\[ = 4x^2 - 20x + 25 \][/tex]
Now, substitute this expression back into [tex]\( G(F(x)) \)[/tex]:
[tex]\[ G(F(x)) = 4x^2 - 20x + 25 + 1 \]\[ G(F(x)) = 4x^2 - 20x + 26 \][/tex]
The circle below is centered at the origin and has a radius of 5 what is it’s equation
Answer:
x^2 + y^2 = 5^2
or x^2 +y^2 = 25
Step-by-step explanation:
The equation of a circle is usually written in the form
(x-h)^2 + (y-k)^2 = r^2
Where (h,k) is the center and r is the radius
The center is at the origin so (h,k) = (0,0) and the radius is 5 so r=5
x^2 + y^2 = 5^2
or x^2 +y^2 = 25
Answer:
x² + y² = 25
Step-by-step explanation:
(x - h)² + (y - k)² = r²
Center ( h⁰, k⁰)
radius = 5/r
(x - 0)² + (y - 0)² = 5² ⇒ x² + y² = 25
This will be your answer : x² + y² = 25
If it takes 10 men 6 days to build a house how long would it take 4
Answer:
15 days
Step-by-step explanation:
10 men : 6 days
4 men : ? days
? = 15
Choose the equation that represents a line that passes through points (-1,2) and (3,1)
A. 4x-y=6
B.x+4y=7
C. x-4y =-9
D.4x+y=2
Answer:
B. x + 4y = 7Step-by-step explanation:
[tex]\text{The point-slope form of an equation of a line:}\\\\y-y_1=m(x-x_1)\\\\m-slope\\(x_1,\ y_1)-point\\\\\text{The formula of a slope:}\\\\m=\dfrac{y_2-y_1}{x_2-x_1}\\\\============================[/tex]
[tex]\text{We have the points:}\ (-1,\ 2)\ \text{and}\ (3,1).\\\\\text{Substitute:}\\\\m=\dfrac{1-2}{3-(-1)}=\dfrac{-1}{4}=-\dfrac{1}{4}\\\\y-2=-\dfrac{1}{4}(x-(-1))\\\\y-2=-\dfrac{1}{4}(x+1)\qquad\text{convert to the standard form}\ Ax+By=C\\\\y-2=-\dfrac{1}{4}(x+1)\qquad\text{multiply both sides by 4}\\\\4y-8=-(x+1)\\\\4y-8=-x-1\qquad\text{add 8 to both sides}\\\\4y=-x+7\qquad\text{add x to both sides}\\\\x+4y=7[/tex]
The equation of a line passing through points (-1, 2) and (3, 1) can be determined using the slope formula, which is (y2 - y1)/(x2 - x1). The resulting slope is -1/4 or -0.25. Unfortunately, none of the provided options match this description.
Explanation:The subject of the question is about finding the equation of a line that passes through the points (-1,2) and (3,1). To find the correct equation, we need to use the formula for the slope of a line which is: (y2 - y1) / (x2 - x1). Plugging in the coordinates (-1,2) and (3,1) will give us a slope of -1/4 or -0.25. This slope should be the coefficient of 'x' in the correct equation. None of the provided choices A, B, C, D have a coefficient of -0.25 for x, therefore, unfortunately, none of these equations represent a line that passes through the points (-1,2) and (3,1).
Learn more about Equation of a Line here:https://brainly.com/question/21511618
#SPJ2
Given that the circles are congruent, can you conclude that ∠jkn is ≅ ∠gfh
Answer:
Yes
Step-by-step explanation:
Think simple.
The picture has already provided us with the information that ∠EFT ≅ ∠LKM, and we also have:
∠EFT ≅ ∠GFH (opposite angles)
∠LKM ≅ ∠JKN (opposite angles as well)
Therefore ∠JKN ≅ ∠GFH
Use synthetic division to solve (x4 – 1) ÷ (x – 1). What is the quotient?
For this case, we must build a quotient that, when multiplied by the divisor, eliminates the terms of the dividend until it reaches the rest.
The attached figure shows the quotient given by:
[tex]x ^ 3 + x ^ 2 + x + 1[/tex]
Answer:
Quotient: [tex]x ^ 3 + x ^ 2 + x + 1[/tex]
See attached image
Answer:
Quotient is: x^3+x^2+x+1
Step-by-step explanation:
We need to solve (x^4-1) ÷ (x-1) using synthetic division.
In synthetic division we write the coefficients in decreasing order of their powers. We have x^4-1 that can be written as: 1x^4 + 0x^3 + 0x^2 + 0x -1
so our coefficients will be
1 0 0 0 -1
and for synthetic division, we take the constant term of divisor and change its sign.
We have x-1, constant term -1 so, our value will be 1.
The division is attached in the figure below.
Quotient is: x^3+x^2+x+1
If f(x) = 2x – 1 and g(x) = x^2 – 2, find [g ◦ f](x).
[tex](g\circ f)(x)=(2x-1)^2-2=4x^2-4x+1-2=4x^2-4x-1[/tex]
Answer:
[tex]4x^2 -4x -1[/tex]
Step-by-step explanation:
Given functions,
[tex]f(x) = 2x - 1-----(1)[/tex]
[tex]g(x) = x^2 -2-----(2)[/tex]
∵ (gof)(x) = g[f(x)] ( Composition of functions )
[tex]\implies (gof)(x) = g(2x-1)[/tex] ( From equation (1) )
[tex]=(2x-1)^2 - 2[/tex] ( From equation (2) )
[tex]=4x^2 + 1 - 4x - 2[/tex]
[tex]=4x^2 -4x -1[/tex]
What is a requirement of adjacent angles?
Adjacent angles must be vertical.
Adjacent angles must be supplementary.
Adjacent angles must share a vertex.
Adjacent angles must share interior points.
Answer:
Adjacent angles must share a vertex.
Step-by-step explanation:
we know that
Two angles are Adjacent when they have a common side and a common vertex
therefore
Adjacent angles must share a vertex.
Answer:
Adjacent angles must share a vertex.
Im so sorry I am so late on answering this question....
Hope the answer (my answer) helps!
f(x) = 4x^2 + 5x + 3; g(x) = 5x - 7, find g(f(x)).
[tex]g(f(x))=5(4x^2+5x+3)-7=20x^2+25x+15-7=20x^2+25x+8[/tex]
Solve for the zeros of the quadratic function f(x) = 9x² + 6x + 1.
Answer:
[tex]\large\boxed{x=-\dfrac{1}{3}}[/tex]
Step-by-step explanation:
[tex]f(x)=9x^2+6x+1\\\\\text{The zeros are for}\ f(x)=0\\\\9x^2+6x+1=0\\\\9x^2+3x+3x+1=0\\\\3x(3x+1)+1(3x+1)=0\\\\(3x+1)(3x+1)=0\\\\(3x+1)^2=0\iff3x+1=0\qquad\text{subtract 1 from both sides}\\\\3x=-1\qquad\text{divide both sides by 3}\\\\x=-\dfrac{1}{3}[/tex]
In an economy without money, there would not be a standard method of measuring___.
Answer:
C) the value of a person's wealth or income
Step-by-step explanation:
If an economy doesn't have money nobody would be wealthy because nobody would have money.
If (a, –5) is a solution to the equation 3a = –2b – 7, what is a?
Question 11 options:
a)
-1
b)
4
c)
0
d)
1
Answer:
d) 1⃣
Step-by-step explanation:
Multiply -5 by -2 to get , then deduct 7 to get 3. So, you now know that 3 = 3a; 1 = a.
using the given points and line, determine the slope of the line. (-3,0) and (2,7)
Answer:
slope = [tex]\frac{7}{5}[/tex]
Step-by-step explanation:
Calculate the slope m using the slope formula
m = (y₂ - y₁ ) / (x₂ - x₁ )
with (x₁, y₁ ) = (- 3, 0) and (x₂, y₂ ) = (2, 7)
m = [tex]\frac{7-0}{2+3}[/tex] = [tex]\frac{7}{5}[/tex]
Hello!
Hint: ⇒ Slope formula: ⇒ [tex]\frac{Y_2-Y_1}{X_2-X_1}[/tex]
[tex]Y_2=7\\ Y_1=0\\\\X_2=2\\X_1=-3[/tex]
[tex]\frac{7-0}{2-(-3)}=\frac{7}{5}[/tex]
[tex]\boxed{\frac{7}{5}}\checkmark[/tex]
[tex]\boxed{\frac{7}{5}}[/tex], which is our correct answer.
Hope this helps you!
Have a great day! :)
Find the area and perimeter of the following figure, please help a.s.a.p
What is the quotient of the polynomials shown below?
Answer:
Option A is correct.
Step-by-step explanation:
We need to find the quotient of the polynomials
[tex](6x^3+8x^2+16)\div(2x+4)[/tex]
The quotient is: 3x^2-2x+4
The remainder is: 0
The division is shown in the figure attached.
Option A is correct.
Find the area of a square with a diagonal of 8 cm.
Answer:
To find the area of a square with only the diagonal known,
Square the diagonal and divide by 2:
8^2 = 64
64/2 = 32
The area is 32 cm^2
Answer:
32
Step-by-step explanation:
I’m correct
The radius of the large sphere is double the radius of the
smal sphere
How many times is the volume of the large sphere than the
small sphere?
Answer:
8 times
Step-by-step explanation:
We know that the radius of smaller sphere is r,
The volume of sphere is given by:
[tex]V_1=\frac{4}{3} \pi r^{3}[/tex]
where V_1 is the volume of the small sphere.
As we know that the radius of large sphere is double of the smaller sphere, the radius of large sphere will be 2r
Let V_2 be the volume of large sphere
[tex]V_2=\frac{4}{3}\pi (2r)^{3} \\ =\frac{4}{3}\pi *8r^3[/tex]
Separating 8 aside
[tex]V_2=8(\frac{4}{3}\pi r^{3})\\V_2=8V_1[/tex]
We can see that the volume of large sphere is eight times the volume of small sphere ..
Answer:
8 times
Step-by-step explanation:
Given
ratio of radii = a : b, then
ratio of volumes = a³ : b³
Here ratio of radii = 1 : 2, hence
ratio of volumes = 1³ : 2³ = 1 : 8
Thus the volume of the large sphere is 8 times the volume of the small sphere
Serena bought 5 shirts for $6 each spent $7 on lunch. she paid for the shirts and lunch using her debit card. The change in the balance of serena’s checking account can be represented by the expression shown. 5(-6) + (-7) which integer represents the change in the balance of serena’s checking account from these purchases? A // -37. B // 23. C // -18. D // 4
Answer:
your answer is A// -37
Step-by-step explanation:
1 shirt=$6
5 shirts= 5 × $6
=$30
lunch= $7
So in total she spent:
$30 + $7= $37
And from what we are given above; the balance in her account is
5(-6) + (-7)
= -30 - 7= -37
4(x-y)^2-12(x-y)(x+y)+9(x+y)^2
Answer:
(x + 5 y)^2
Step-by-step explanation:
Simplify the following:
4 (x - y)^2 - 12 (x - y) (x + y) + 9 (x + y)^2
(x - y) (x - y) = (x) (x) + (x) (-y) + (-y) (x) + (-y) (-y) = x^2 - x y - x y + y^2 = x^2 - 2 x y + y^2:
4 x^2 - 2 x y + y^2 - 12 (x - y) (x + y) + 9 (x + y)^2
4 (x^2 - 2 x y + y^2) = 4 x^2 - 8 x y + 4 y^2:
4 x^2 - 8 x y + 4 y^2 - 12 (x - y) (x + y) + 9 (x + y)^2
(x + y) (x - y) = (x) (x) + (x) (-y) + (y) (x) + (y) (-y) = x^2 - x y + x y - y^2 = x^2 - y^2:
4 x^2 - 8 x y + 4 y^2 - 12 x^2 - y^2 + 9 (x + y)^2
-12 (x^2 - y^2) = 12 y^2 - 12 x^2:
4 x^2 - 8 x y + 4 y^2 + 12 y^2 - 12 x^2 + 9 (x + y)^2
(x + y) (x + y) = (x) (x) + (x) (y) + (y) (x) + (y) (y) = x^2 + x y + x y + y^2 = x^2 + 2 x y + y^2:
4 x^2 - 8 x y + 4 y^2 - 12 x^2 + 12 y^2 + 9 x^2 + 2 x y + y^2
Grouping like terms, 4 x^2 - 8 x y + 4 y^2 - 12 x^2 + 12 y^2 + 9 (x^2 + 2 x y + y^2) = 9 (x^2 + 2 x y + y^2) + (4 y^2 + 12 y^2) - 8 x y + (4 x^2 - 12 x^2):
9 (x^2 + 2 x y + y^2) + (4 y^2 + 12 y^2) - 8 x y + (4 x^2 - 12 x^2)
4 y^2 + 12 y^2 = 16 y^2:
9 (x^2 + 2 x y + y^2) + 16 y^2 - 8 x y + (4 x^2 - 12 x^2)
4 x^2 - 12 x^2 = -8 x^2:
9 (x^2 + 2 x y + y^2) + 16 y^2 - 8 x y + -8 x^2
9 (x^2 + 2 x y + y^2) = 9 x^2 + 18 x y + 9 y^2:
9 x^2 + 18 x y + 9 y^2 + 16 y^2 - 8 x y - 8 x^2
Grouping like terms, 9 x^2 + 18 x y + 9 y^2 + 16 y^2 - 8 x y - 8 x^2 = (9 y^2 + 16 y^2) + (18 x y - 8 x y) + (9 x^2 - 8 x^2):
(9 y^2 + 16 y^2) + (18 x y - 8 x y) + (9 x^2 - 8 x^2)
9 y^2 + 16 y^2 = 25 y^2:
25 y^2 + (18 x y - 8 x y) + (9 x^2 - 8 x^2)
x y 18 + x y (-8) = 10 x y:
25 y^2 + 10 x y + (9 x^2 - 8 x^2)
9 x^2 - 8 x^2 = x^2:
25 y^2 + 10 x y + x^2
The factors of 25 that sum to 10 are 5 and 5. So, 25 y^2 + 10 x y + x^2 = (x + 5 y) (x + 5 y):
(x + 5 y) (x + 5 y)
(x + 5 y) (x + 5 y) = (x + 5 y)^2:
Answer: (x + 5 y)^2
[tex]4(x-y)^2-12(x-y)(x+y)+9(x+y)^2 =\\4(x^2-2xy+y^2)-12(x^2-y^2)+9(x^2+2xy+y^2)=\\4x^2-8xy+4y^2-12x^2+12y^2+9x^2+18xy+9y^2=\\x^2+10xy+25y^2[/tex]
which can factorised into [tex](x+5y)^2[/tex]
What is nine and two hundredths as a decimal?
Step-by-step explanation:
9.02
remember when dealing with decimals:
0.(tenth)(hundredths)(thousandths)
Nine and two hundredths as a decimal is 9.02.
Explanation:The question asks for the decimal representation of nine and two hundredths. In the decimal number system, 'and' corresponds to the decimal point. So, the answer to the question is 9.02. This is because the 'nine' is in the whole number part before the decimal point and 'two hundredths' is represented by '02' after the decimal point.
Learn more about Decimal representation here:https://brainly.com/question/35491860
#SPJ2
SOMEONE HELP PLEASE!
Answer:
EStep-by-step explanation:
[tex]a\ \vee\ b\ \text{is true if }\ a=T\ \text{or}\ b=T.\\\\\text{Therefore}\ p\ \vee\ (q\ \wedge\ r)\ \text{is\ true,\ if}\ p=T\ \text{or}\ (q\ \wedge\ r)=T.\\\\\text{We have}\ p=F.\ \text{Therefore}\ p\ \vee\ (q\ \wedge\ r)\ \text{is true, if}\ (q\ \wedge\ r)=T.[/tex]
which equations represent the line that is perpendicular to the line 5x - 2y = -6 and passes through the point (5, -4) select all that apply
Answer:
the answers are A B AND D
Step-by-step explanation:
To find perpendicular lines you take the slope and change the sign and find the reciprocal. after doing that you set it up as a new equation that you will use to find b using the point.
in this case
y= - 2/5x +b
plug in the x and y values of the point (5, -4) to find b
b= -2
you put that together to get the equation
The equation of the line that is perpendicular to the line 5x - 2y = -6 and passes through the point (5, -4) is y = -0.4x - 2.
Explanation:The given equation is 5x - 2y = -6. First step is to convert this to the slope-intercept form (y = mx + b) to find the slope. To do this, solve for y in terms of x, which looks like y = 2.5x + 3. The perpendicular line would have a slope that is the negative reciprocal this slope (m = -1/2.5 or -0.4).
Next, apply the point-slope formula (y - y1 = m(x - x1)) where m is the slope and (x1, y1) is the point that the line passes through. In this case, (x1, y1) is (5, -4), and slope m is -0.4. Then, y - (-4) = -0.4(x - 5), results to y + 4 = -0.4x + 2, finally gives y = -0.4x - 2 as the equation of the line that is perpendicular to 5x - 2y = -6 and passes through the point (5, -4).
Learn more about Perpendicular Lines here:https://brainly.com/question/18271653
#SPJ3